Pengaruh Penggunaan Aplikasi Wattpad Terhadap Perilaku Remaja - Ardian Setio Utomo; Dewi Warhamni; Tsanya Marghereta (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2022)
Technology that continues to develop makes the internet become a medium to disseminate  messages that can influence people's behavior. Wattpad is a site and blogging application that is currently in demand by teenager. However, teenager who often act impulsively can experience changes in behavior after reading novels on the Wattpad application. Based on this matter, then this study aims to determine the effect of using the Wattpad application on teenage behavior. This study used a quantitative method to examine the effect of using the Wattpad application on teenage behavior. Sampling was done by purposive sampling technique. There were 100 respondents who were the users of Wattpad application throughout Indonesia. Data was collected using an online questionnaire and then processed using SPSS version 28 for the classical assumption test, simple linear regression analysis, t test, and the coefficient of determination. The results show that the use of the Wattpad application has an influence on teenage behavior by 58.2% and the remaining 41.8% was influenced by other factors not examined in this study.